Noninvasive assessment of articular cartilage surface damage using reflected polarized light microscopy - Huynh, Ruby N; Nehmetallah, George; Raub, Christopher B (Journal of biomedical optics, 2017)
Articular surface damage occurs to cartilage during normal aging, osteoarthritis, and in trauma. A noninvasive assessment of cartilage microstructural alterations is useful for studies involving cartilage explants. This study evaluates polarized reflectance microscopy as a tool to assess surface damage to cartilage explants caused by mechanical scraping and enzymatic degradation. Adult bovine articular cartilage explants were scraped, incubated in collagenase, or underwent scrape and collagenase treatments. In an additional experiment, cartilage explants were subject to scrapes at graduated levels of severity. Polarized reflectance parameters were compared with India ink surface staining, features of histological sections, changes in explant wet weight and thickness, and chondrocyte viability. The polarized reflectance signal was sensitive to surface scrape damage and revealed individual scrape features consistent with India ink marks. Following surface treatments, the reflectance contrast parameter was elevated and correlated with image area fraction of India ink. After extensive scraping, polarized reflectance contrast and chondrocyte viability were lower than that from untreated explants. As part of this work, a mathematical model was developed and confirmed the trend in the reflectance signal due to changes in surface scattering and subsurface birefringence. These results demonstrate the effectiveness of polarized reflectance microscopy to sensitively assess surface microstructural alterations in articular cartilage explants.